Study on Spatial Evolution of Chinese Green Building. (June 2019) - Hao, T; Wang, J
Abstract: Green building is an important part of ecological civilization construction in China, which is also a significant reflection of national developing under a new type of urbanization [1]. Since 2006, the number and total gross floor area of green building has achieved major development with the promulgation and implement of national and local standards and promotions of green building. However, this rapid development shows an obvious regional difference and imbalance. This paper conducts a quantitative study by using geospatial statistics theory and geographic information system technique. It aims to explore characteristics and the driven factor of green buildings' spatial evolution so that the development level of green building could be evaluated based on much more scientific and reasonable method. It also aims at providing theory supporting as well as reference for policy making to stimulate green building development in a more balanced way.